MULTILEVEL ENKRIPSI MENGGUNAKAN KOMBINASI ALGORITMA KRIPTOGRAFI BASE64 DAN PEPPER - Muhammad Najibulloh Muzaki; Rina Firliana; Rini Indriati; Anita Sari Wardani; Erna Daniati (Universitas Islam Balitar Blitar, 2025)
Data exchange over the internet is susceptible to security issues. Efforts to secure the system are carried out using various methods. One method used is to encrypt data. This research uses a combination of Base64 and Pepper encryption methods. The Base64 algorithm is a two-way hashing algorithm which is used to encrypt and decrypt data. The Pepper algorithm is used to insert several characters into the data. The combination of the two algorithms uses multilevel techniques. From the test results it can be seen that the application of the combination of the Base64 and Pepper algorithms provides more complex encryption results when compared to the results from the pure Base64 algorithm. because it produces unrecognizable characters.